Problem-Based Inquiry Method: Improving Critical Thinking Skills, Academic Outcomes, and Learning Motivation - Christina Ismaniati; Almendo Thio Lindra; Heldy Adynata Putra Pratama (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study investigates how well the Problem-Based Inquiry Method (PBIM) improves academic performance, learning motivation, and critical thinking abilities. Innovative techniques are required since traditional education methods frequently fall short in fostering intellectual curiosity and higher-order cognitive skills. Inquiry-based learning and problem-solving are combined in PBIM to encourage active student participation. A control group (n=67) that received traditional instruction was contrasted with an experimental group (n=66) that used PBIM in a quasi-experimental design. Motivation surveys, subject-specific posttests, and standardized critical thinking tests were used to gather data, which were then subjected to t-tests and MANOVA analysis. The experimental group's critical thinking (mean difference = 22.82, p=0.000), academic results (mean difference = 8.69, p=0.000), and motivation (mean difference = 16.12, p=0.000) all showed significant gains, according to the results. The multivariate influence of PBIM was validated by MANOVA (p<0.05). The results support the inclusion of PBIM in educational practices to replace passive learning paradigms by highlighting its effectiveness in promoting cognitive development, academic achievement, and intrinsic motivation.